A Survey on Advanced Control Approaches in Factory Automation. Issue 3 (2015) - Dotoli, Mariagrazia; Fay, Alexander; Miśkowicz, Marek; Seatzu, Carla
Abstract: The goal of this paper consists in providing a survey of the main advanced control techniques currently adopted in factory automation. In particular, attention is devoted to model based control, model predictive control, intelligent and adaptive control, discrete event and event- triggered control. Open issues and challenges are pointed out, and the needs for further research efforts are discussed in detail.